Pengecualian terhadap Penerapan Asas Ultra Petitum Partium dalam Beracara di Pengadilan Agama - Mrs. Hartini (Fakultas Hukum Universitas Gadjah Mada, 2009)
A judge must examine and adjudicate all charges thoroughly on the lawsuit brought to the court. The judge should not only examine and adjudicate part of the charge and disregard the rest. On the other hand, judge in his/her adjudication is prohibited to accede above the suit brought by the parties. This prohibition is called ultra petitum partium. A judge who accedes in excess of the suit partium is considered to be exceeding his/her authority. In Religious Court proceedings, the implementation of ultra petitum partium principle is an exception in several types of cases. In the procedure of divorce (cerai talak), a judge may grant something not demanded by wife either in the petition of divorce or in the reconvention by charging certain obligations upon the husband, which is the wife’s right as the consequence of the separation. In the procedure of divorce, judge may order a preliminary injunction even if such injunction is not demanded. The argument that justifies the judge’s action is the Marriage Act and the procedural law in the Act on Religious Court is a lex specialis stipulation, judge as judge made law must dig into the values of life, and the judge may execute contra legem action if the stipulation in an article considered to be in contradiction with justice and benefit.